Urban climate mapping in Bragança (Portugal). Preliminary results from UHI effect analysis - Gonçalves, Artur (2013)
Urban climate mapping (UCMap) is a complex yet necessary activity that should be considered in the urban planning process. Although there has been a wide development of UCMap across different countries, mapping methods must be further improved and cover a wider diversity of geographic locations (Ren, 2010). As part of the transnational BIOURB project, an UCMap of Bragança (Portugal) is being developed aiming at informing the local Planning Authorities, while establishing a basic methodology that can be used as a reference for the Northern Portuguese and Castilla-León (Spain) cities. The methodology can be described by the implementation of two combined approaches: a urban climate monitoring and a climate model. Urban climate is being studied by means of meteorological monitoring, combining the use of temperature and relative humidity sensors (23), wind anemometers (5) and weather stations (3). The location of these equipments was established to equally address seven different Local Climate Zones (LCZ) (based on Stewart and Oke, 2009) and to express the eventual gradient from rural to urban. The Poster presents the preliminary results focusing on the initial findings concerning temperature differences across LCZ, the effects of wind speed on such processes and amplitude of the Urban Heat Island (UHI).